Changes in the prevalence of severe anxiety and depression symptoms and the associated factors in adults living in Manaus: a comparison of two cross-sectional studies conducted in 2015 and 2019 - Vanessa Gomes Lima; Marcus Tolentino Silva; Gustavo Magno Baldin Tiguman; Taís Freire Galvão (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Emotional distress increases, also affected by the setting. OBJECTIVE: To estimate changes in prevalence of severe anxiety and depressive symptoms and associated factors. DESIGN AND SETTING: This cross-sectional study included adults living in Manaus selected through a three-stage probability sampling in 2015 and 2019. METHODS: This is an analysis of two surveys conducted. The outcomes were assessed by Generalized Anxiety Disorder 7-item (≥ 15 points) and Patient Health Questionnaire 9-item (≥ 20), and changes were tested by chi-square goodness-of-fit. Prevalence ratios (PR) with 95% confidence intervals (95%CI) were calculated by Poisson regression. RESULTS: Severe anxiety symptoms increased from 3.3% (95%CI = 2.7–3.9) in 2015 (n = 3,479) to 8.7% (95%CI = 7.5–9.8) in 2019 (n = 2,321); severe depressive symptoms changed from 2.5% (95%CI = 2.0–3.0) to 8.5% (95%CI = 7.3–9.6). Variations were more pronounced in social vulnerability (P < 0.05). Outcomes were higher in women (anxiety: PR = 1.27; 95%CI = 1.20–1.34, depression: PR = 1.35; 95%CI = 1.27–1.44), low-income individuals (anxiety: PR = 1.90; 95%CI = 1.20–3.00, depression: PR = 1.98; 95%CI = 1.22–3.19), less educated individuals (anxiety: PR = 2.20; 95%CI = 1.16–4.18, depression: PR = 2.37; 95%CI = 1.23–4.60), and individuals with poor health status (anxiety: PR = 9.06; 95%CI = 6.72–12.21, depression: PR = 8.99; 95%CI = 6.67–12.12). CONCLUSION: Severe anxiety and depression tripled in Manaus, potentially reflecting Brazilian socioeconomic crises.